Aspek Hukum Islam Terhadap Keabsahan Pernikahan Pasangan Mualaf Yang Tidak Melakukan Isbath Nikah - Djafar, Fadlun Nur Fadilah; Susilawati, Susi; Ansar, Ansar; Arfan, Arfan (LPPM Institut Pendidikan Nusantara Global, 2025)
Marriage is a legal and social institution that forms the foundation of a civilized society. In Indonesia, marriage is not only seen as a relationship between two individuals based on love and responsibility but also as a legal event that creates juridical consequences. The inconsistency between Islamic law and Indonesian positive law often creates legal challenges, particularly for mualaf (converts to Islam) couples who perform religious marriages without state registration (isbat nikah). This issue becomes complex because, under Islamic law, a marriage is considered valid if it fulfills the pillars and requirements of nikah, while under Indonesian positive law, registration is an essential condition for the marriage to have legal force. As a result, significant implications arise regarding legal status, civil rights, and the protection of women and children resulting from such marriages. This article employs a normative juridical approach by analyzing statutory regulations, the Compilation of Islamic Law (KHI), court decisions, and field interviews with officials from the Office of Religious Affairs (KUA) in Sigi Biromaru District. The findings reveal that unregistered marriages among mualaf couples cause legal vulnerability for women and children, as their status is not recognized administratively. Furthermore, the implementation of isbat nikah has not been fully effective due to a lack of public understanding of legal procedures. This study recommends the harmonization of Islamic and positive law through the integration of substantive justice values to achieve the ultimate purposes of law justice, certainty, and benefit.